Efficacy and Acceptability of Interventions for Attenuated Positive Psychotic Symptoms in Individuals at Clinical High Risk of Psychosis: A Network Meta-Analysis - Davies, Cathy; Radua, Joaquim; Cipriani, Andrea; Stahl, Daniel; Provenzani, Umberto; McGuire, Philip; Fusar-Poli, Paolo (Frontiers in Psychiatry, 2018)
Background Attenuated positive psychotic symptoms represent the defining features of the clinical high-risk for psychosis (CHR-P) criteria. The effectiveness of each available treatment for reducing attenuated positive psychotic symptoms remains undetermined. This network meta-analysis (NMA) investigates the consistency and magnitude of the effects of treatments on attenuated positive psychotic symptoms in CHR-P individuals, weighting the findings for acceptability. Methods Web of Science (MEDLINE), PsycInfo, CENTRAL and unpublished/grey literature were searched up to July 18, 2017. Randomized controlled trials in CHR-P individuals, comparing at least two interventions and reporting on attenuated positive psychotic symptoms at follow-up were included, following PRISMA guidelines. The primary outcome (efficacy) was level of attenuated positive psychotic symptoms at 6 and 12 months; effect sizes reported as standardized mean difference (SMD) and 95% CIs in mean follow-up scores between two compared interventions. The secondary outcome was treatment acceptability (reported as odds ratio (OR)). NMAs were conducted for both primary and secondary outcomes. Treatments were cluster-ranked by surface under the cumulative ranking curve values for efficacy and acceptability. Assessments of biases, assumptions, sensitivity analyses and complementary pairwise meta-analyses for the primary outcome were also conducted. Results Overall, 1707 patients from 14 studies (57% male, mean age= 20) were included. In the NMA for efficacy, ziprasidone + Needs-Based Intervention (NBI) was found to be superior to NBI (SMD= -1.10, 95% CI -2.04 to -0.15), Cognitive Behavioural Therapy-French & Morrison protocol (CBT-F) + NBI (SMD= -1.03, 95% CI -2.05 to -0.01), and risperidone + CBT-F + NBI (SMD= -1.18, 95% CI -2.29 to -0.07) at 6 months. However, these findings did not survive sensitivity analyses. For acceptability, aripiprazole + NBI was significantly more acceptable than olanzapine + NBI (OR= 3.73; 95% CI 1.01 to 13.81) at 12 months only. No further significant NMA effects were observed at 6 or 12 months. The results were not affected by inconsistency or evident small-study effects, but only two studies had an overall low risk of bias. Conclusion On the basis of the current literature, there is no robust evidence to favour any specific intervention for improving attenuated positive psychotic symptoms in CHR-P individuals.